2014
DOI: 10.1534/genetics.114.169797
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Competes for a Common Phosphatidylethanolamine Pool with Major Cellular PE-Consuming Pathways in Saccharomyces cerevisiae

Abstract: Autophagy is a highly regulated pathway that selectively degrades cellular constituents such as protein aggregates and excessive or damaged organelles. This transport route is characterized by engulfment of the targeted cargo by autophagosomes. The formation of these double-membrane vesicles requires the covalent conjugation of the ubiquitin-like protein Atg8 to phosphatidylethanolamine (PE). However, the origin of PE and the regulation of lipid flux required for autophagy remain poorly understood. Using a gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Bürgermeister et al also observed that a certain portion of PE synthesized by Psd2 can be imported into mitochondria with a moderate efficiency (Bürgermeister et al, 2004). In addition, some data have suggested that autophagy competes for a common PE pool with major cellular PE-consuming pathways, such as glycosylphosphatidylinositol anchoring (Wilson-Zbinden et al, 2015). Considering lipid trafficking and the major role of autophagy, our results are therefore not so surprising.…”
Section: Discussionsupporting
confidence: 61%
“…Bürgermeister et al also observed that a certain portion of PE synthesized by Psd2 can be imported into mitochondria with a moderate efficiency (Bürgermeister et al, 2004). In addition, some data have suggested that autophagy competes for a common PE pool with major cellular PE-consuming pathways, such as glycosylphosphatidylinositol anchoring (Wilson-Zbinden et al, 2015). Considering lipid trafficking and the major role of autophagy, our results are therefore not so surprising.…”
Section: Discussionsupporting
confidence: 61%
“…Overexpression of Pem1p is lethal to the mcd4-ts yeast strain presumably by increasing the conversion of PE to PC, thus reducing the pool of PE available for GPI anchor formation. Consistent with this idea, reducing cellular PE levels by deleting PSD2 or disrupting the CDP-ethanolamine pathway also impairs growth of the mcd4-ts yeast strain (Wilson-Zbinden et al, 2015). The availability of PE as a substrate for these processes is a potentially limiting factor that may regulate flux through each pathway.…”
Section: Cellular and Molecular Functions Of Pementioning
confidence: 74%
“…Further, PE produced by either the CDP-ethanolamine or decarboxylation pathways can be converted to PC (Kennedy and Weiss, 1956; Ridgway and Vance, 1987). PE is also a critical substrate for at least two fundamental posttranslational modifications, GPI anchors (discussed later; Menon and Stevens, 1992; Wilson-Zbinden et al, 2015) and lipidation of Atg8p/LC-3 (discussed in Section 4.4; Ichimura et al, 2000). …”
Section: Pe Biosynthesis and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent of its role in GPI biosynthesis, Mcd4 is implicated in transport‐dependent metabolism of phosphatidylserine and non‐mitochondrial ATP transport across membranes . Furthermore, Mcd4 uses EtnP from a common pool of PE which is also used in the biosynthesis of phosphatidylcholine and in the formation of autophagosomes . Not surprisingly, deleting CHO2 (PE‐ N‐ methyltransferase) or ATG7 (an autophagy related gene) rescues the mcd4 mutant while simultaneously restoring lipidation and proper membrane localization of Gas1, a GPI‐AP .…”
Section: Addition Of Man and Etnp Residuesmentioning
confidence: 99%